2017
DOI: 10.1038/ncomms15016
|View full text |Cite|
|
Sign up to set email alerts
|

Exosome-delivered EGFR regulates liver microenvironment to promote gastric cancer liver metastasis

Abstract: The metastatic organotropism has been one of the cancer's greatest mysteries since the ‘seed and soil' hypothesis. Although the role of EGFR in cancer cells is well studied, the effects of secreted EGFR transported by exosomes are less understood. Here we show that EGFR in exosomes secreted from gastric cancer cells can be delivered into the liver and is integrated on the plasma membrane of liver stromal cells. The translocated EGFR is proved to effectively activate hepatocyte growth factor (HGF) by suppressin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
363
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 434 publications
(393 citation statements)
references
References 42 publications
4
363
0
2
Order By: Relevance
“…ANXA1 might be responsible for the recruitment of phospho-EGFR into exosomes, and this might be mediated by an (transient) interaction of ANXA1 and phospho-EGFR which has already been reported [33]. Exosomal EGFR has been linked to organ-specific metastasis by influencing premetastatic niche formation and to tumour immunity by inducing tolerance in recipient dendritic cells and as a consequence tumour antigen-specific regulatory T cells [36,37]. In summary, ANXA1 seems to be located at the interface of inflammation and cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ANXA1 might be responsible for the recruitment of phospho-EGFR into exosomes, and this might be mediated by an (transient) interaction of ANXA1 and phospho-EGFR which has already been reported [33]. Exosomal EGFR has been linked to organ-specific metastasis by influencing premetastatic niche formation and to tumour immunity by inducing tolerance in recipient dendritic cells and as a consequence tumour antigen-specific regulatory T cells [36,37]. In summary, ANXA1 seems to be located at the interface of inflammation and cancer.…”
Section: Discussionmentioning
confidence: 99%
“…ANXA1 protein levels affect exosome production and the release of exosomal phospho-EGFR Recent findings have demonstrated an important role of exosomal EGFR in metastasis formation. As ILVs can be precursors of exosomes, we speculated that ANXA1 may regulate exosomal EGFR release [35,36]. Extracellular vesicles of HN5 Ctrl and ANXA1 knockdown cells were isolated by ultracentrifugation and characterised by nanoparticle tracking analysis.…”
Section: Anxa1 Regulates Egfr Signallingmentioning
confidence: 99%
See 1 more Smart Citation
“…TEX induce angiogenesis via transportation of paracrine signaling factors and pro-angiogenic molecules including epidermal growth factor receptor (EGFR) mRNA (42). Zhang et al (43) recently verified that gastric cancer-derived exosomes served an important role in liver metastasis; EGFR levels were enriched in exosomes isolated from the serum of gastric cancer patients but not in healthy subject serum exosomes, and the number of serum exosomes increased with the staging of gastric cancer. In a mouse experiment, it was identified that exosomes of the SGC7901 gastric carcinoma cell line could transport EGFR into the liver and ultimately to the membrane of stromal liver cells.…”
Section: Exosomes In Peritoneal Dissemination Of Gastric Cancermentioning
confidence: 99%
“…In a mouse experiment, it was identified that exosomes of the SGC7901 gastric carcinoma cell line could transport EGFR into the liver and ultimately to the membrane of stromal liver cells. As a consequence, SGC-exosome-derived EGFR activated liver hepatocyte growth factor (HGF) by suppressing expression of the microRNA (miRNA/miR) miR-26a/b, establishing the liver as an ideal site for tumor cell metastasis (43). The EGFR positivity rate of metastatic tumors in patients with peritoneal metastasis is reportedly significantly higher (70.1%) than that of metastatic tumors in patients with liver metastasis (37.5%) (44), which indicates that EGFR expression is associated with peritoneal metastasis.…”
Section: Exosomes In Peritoneal Dissemination Of Gastric Cancermentioning
confidence: 99%